Role of the collagen receptor DDR1 in epithelial morphogenesis and polarisation - Søgaard, P (2017)
During development of epithelial organs, epithelial cells collectively migrate and invade into their surroundings to form complex 3D structures, such as the tubular ducts and alveoli of the mammary gland. A prerequisite for coordinating such collective movement is apicobasal cell polarity. This polarity divides the plasma membrane of epithelial cells into an apical domain towards the lumen of structures and a basal domain facing the matrix. Polarity is essential for the functionality of epithelial tissues and signals from the surrounding matrix are known to participate in its establishment. In contrast, loss of polarity has been associated with progression of diseases such as cancer. During epithelial tubulogenesis, the pro-invasive enzyme MT1-MMP is regulated according to apicobasal polarity. This regulation is essential for tubulogenesis to occur and restricts MT1-MMP activity to the tip of protruding tubules by ensuring that the enzyme only localises to the basal, matrix-abutting cell surface in this location. Signals from fibrillar collagen I contribute to regulating the polarised distribution of MT1-MMP. How such signals are transmitted and influence polarised trafficking is however not understood. In this study, I found that inhibition of the collagen receptor DDR1 disturbed the apicobasal distribution of MT1-MMP in MDCK cells. In 3D environments, DDR1 inhibition blocked MT1-MMP-dependent tubulogenesis of epithelial cells, which instead formed compact, multi-layered aggregates. Furthermore, polarisation of the epithelial cell membrane into an apical and a basal domain failed in absence of DDR1 signalling, suggesting that DDR1 affects establishment of epithelial polarity. In support of this, the effects of DDR1 signalling on apicobasal polarity were not limited to MT1-MMP- dependent morphogenesis, but also proved essential for polarisation of cells during 3D morphogenesis that did not require ECM degradation. An investigation of signalling downstream of DDR1 in establishment of apicobasal polarity revealed this to involve modulation of cytoskeletal tension. Inhibition of DDR1 in 2D culture of MDCK cells thus increased ROCK-dependent phosphorylation of MLC along cell-cell junctions, suggesting that DDR1 can suppress ROCK activity. Importantly, the ROCK-suppressing function of DDR1 contributed to establishment of polarity in MDCK cells in 3D matrices, where inhibition of ROCK activity rescued the formation of polarised cysts in absence of DDR1 signalling. The role of DDR1 in epithelial organisation was reflected in the epithelium of the mammary gland of lactating DDR1-null mice, which had smaller alveoli with a diffuse distribution of basement membrane components compared to wild type mice. Furthermore, DDR1 inhibition attenuated formation of milk-producing mammospheres during lactogenic differentiation of mammary epithelial cells in vitro in a ROCK- dependent manner. This suggests that the ROCK-suppressing function of DDR1 observed in MDCK cells is important for morphogenesis of other epithelial cell types as well. Overall, this study suggests that DDR1 signalling contributes to epithelial polarisation and morphogenesis in a manner involving regulation of cytoskeletal organisation, at least partly through regulation of ROCK activity.